"Bis‐Click" Ligation of DNA: Template‐Controlled Assembly, Circularisation and Functionalisation with Bifunctional and Trifunctional Azides. Issue 14 (12th January 2017) - Yang, Haozhe; Seela, Frank
Abstract: Ligation and circularisation of oligonucleotides containing terminal triple bonds was performed with bifunctional or trifunctional azides. Both reactions are high yielding. Template‐assisted bis‐click ligation of two individual non‐complementary oligonucleotide strands was accomplished to yield heterodimers exclusively. In this context, the template fulfils two functions: it accelerates the ligation reaction and controls product assembly (heterodimer vs. homodimer formation). Intermolecular bis‐click circularisation of one oligonucleotide strand took place without template assistance. For construction of oligonucleotides with terminal triple bonds in the nucleobase side chain, 7‐ or 5‐functionalised 7‐deaza‐dA and dU residues were used. These oligonucleotides are directly accessible by solid‐phase synthesis. When trifunctional azides were employed instead of bifunctional linkers, functionalisation of the remaining azido group was performed with small molecules such as 1‐ethynyl pyrene, biotin propargyl amide or with ethynylated oligonucleotides. By this means, branched DNA was constructed. Abstract : "Bis‐click" chemistry : Azido‐DNAs constructed by template‐assisted ligation and circularisation utilising multifunctional azides and alkynylated oligonucleotides were functionalised with various alkynyl molecules (see scheme).